Produksi Bahan Bakar Minyak Dari Limbah Plastik Hdpe Dan Pete 1 Kg - Sumartono Sumartono (Fakultas Teknik UMSU, 2019)
Waste plastic waste is very difficult to decompose. There are several solutions to overcome this, including can be processed into granules, these granules as recycled raw materials for the manufacture of other materials. In addition, plastic waste can be processed into fuel oil (BBM). The purpose of this study is to produce BBM products from various types of plastic waste by the pyrolysis method. Waste samples of HDPE and PETE plastic with each sample amount 1 kg to 1.5 kg (produce 450 ml and 220 ml BBM). The Heat Value produced is only one type of plastic waste that is close to PT. Pertamina products, namely BBM HDPE with a heating value of 11420 kcal / kg, diesel oil PT. Pertamina, (10,550 to 11,667 kcal / kg). Other types of plastic are higher. It is recommended that the plastic waste processing equipment must be increased in capacity and can function continuously without stopping the combustion process, needing to be equipped with plastic waste chopper and rinsing equipment so that its capacity increases and is efficient.